2018
DOI: 10.1093/treephys/tpy017
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate dynamics of three dominant species in a Chinese savanna under precipitation exclusion

Abstract: The potential impact of drought on the carbon balance in plants has gained great attention. Non-structural carbohydrate (NSC) dynamics have been suggested as an important trait reflecting carbon balance under drought conditions. However, NSC dynamics under drought and the response mechanisms of NSC to drought remain unclear, especially in water-limited savanna ecosystems. A precipitation exclusion experiment was performed to simulate different drought intensities in a savanna ecosystem in Yuanjiang valley in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Therefore, NSCs in gymnosperms and angiosperms may respond differently to drought (Johnson et al, 2012). However, the impact of drought stress on NSCs is still inconclusive: Some studies have found NSCs reduction in trees under drought (Adams et al, 2013; Galiano, Martínez‐Vilalta, & Lloret, 2011; Piper, 2011), some studies have found that drought stress has no significant effect on NSCs levels (Gruber, Pirkebner, & Florian, 2012; Jin et al, 2018), and other studies have shown NSCs increase under drought (Correia et al, 2018; Crous et al, 2011; Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, NSCs in gymnosperms and angiosperms may respond differently to drought (Johnson et al, 2012). However, the impact of drought stress on NSCs is still inconclusive: Some studies have found NSCs reduction in trees under drought (Adams et al, 2013; Galiano, Martínez‐Vilalta, & Lloret, 2011; Piper, 2011), some studies have found that drought stress has no significant effect on NSCs levels (Gruber, Pirkebner, & Florian, 2012; Jin et al, 2018), and other studies have shown NSCs increase under drought (Correia et al, 2018; Crous et al, 2011; Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of drought on NSCs are related to drought characteristics such as intensity and duration (Anderegg & Anderegg, 2013; Jin et al, 2018; Sala, Woodruff, & Meinzer, 2012). The impact of slight or moderate drought on trees is a gradual process with a slow formation of cavitation followed by slow repair.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation reduction experimental plots were set up using rainout shelters, which were described in more detail in Jin, Li, Liu, Liu, Zhang, Sha, et al. (a). The rainout shelters were constructed with a steel frame (7 m in height) and covered with transparent 1.2‐mm polyethylene sheets (permitting over 85% penetration of photosynthetically active radiation) to reduce the net input of precipitation to the soil.…”
Section: Methodsmentioning
confidence: 99%
“…In order to disentangle the effects of declines in precipitation on plant community structure and composition of savannas, a precipitation manipulation experiment was conducted. Precipitation reduction significantly decreased the growth of woody species in this savanna ecosystem, but the community composition of the overstorey remained unchanged (Jin, Li, Liu, Liu, Zhang, Sha, et al., a). We know little about the impact of precipitation reduction on the community dynamics of the understorey herbaceous layer, so a four‐year study was performed to explore the response of the herbaceous community to declines in precipitation.…”
Section: Introductionmentioning
confidence: 98%
“…The study was conducted at the Yuanjiang Savanna Ecosystem Research Station (23°27′N, 102°10′E, and 551 m above sea level) of the Xishuangbanna Tropical Botanical Garden, Chinese Academy of Sciences, in Yunnan province of southwestern China. The soil in the region is classified as ferralic cambisol according to the FAO classification (Jin et al, 2018). Dominant species in this savanna are Lannea coromandelica, Polyalthia cerasoides, Campylotropis delavayi and Heteropogon contortus (Jin and Ou, 2000).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%